Distinctive presentation of pinna squamous cell carcinoma as devil cutaneous horn - Hussain, Tanvir; Salazar, Jony; Khanam, Mohosana; Attique, Sarwar; Alaqeab, Enas; Matin, Abdul (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Cutaneous horns are considered rare clinical elements defined by compact exophytic keratin growth typically resembling an animal’s horn. They are prone in the body’s sun-exposed areas, arising from various benign, malignant and premalignant conditions. Therefore, this paper reflects a reported case for the 75-year-old male diagnosed with cutaneous horn in his right pinna. The histopathological evaluation confirmed a squamous cell carcinoma (SCC). The case has equally stressed why histopathological assessment or examination is necessary to determine the condition’s nature and proper management. The patient was taken through a wide local excision with a comprehensive assessment and evaluation and the multidisciplinary discussion with an oncology and head expertise team. From the case, it is necessary to practice vigilance and caution in diagnosing and managing the condition from unusual places like the ear.